Smart Remote Control through Android - M. Jyothirmai; M. Pravallika; P. Maheswari; P. Suhana; S. Nikhitha (Journal of Electronic Design Engineering, 2022)
The main aim of this project is to develop a home automation system with Android application controlled remote. Switches in modern homes are rapidly being replaced by wirelessly operated ones as part of a centralized control system. Normal wall switches are positioned around the house, making it challenging for the user to approach them and activate them. Smart Remote operation can be done by any Android phone/Tab etc., with the help of Android Operating System, along with a touch screen operation based on GUI (Graphical User Interface). In order to get this output, Android mobile acts as a transmitter, this sends ON/OFF commands. Operating the particular remote switch on the transmitter, the loads can be turned ON/OFF remotely through wireless technology.